Risk Of Occurrence: Analysis Of Maternal And Perinatal Outcomes In Teenage Pregnancy At Rsi Aminah Blitar - ekasejati, Putri; Wiranti Dwi Novita Isnaeni,; Reni Yuli Astutik,; Atik Setiawan W, (Journal of Health Science Community, 2026)
Teenage pregnancy remains a leading cause of maternal and neonatal mortality, posing significantly higher risks compared to pregnancies in the standard reproductive age. This study aimed to investigate the influence of teenage pregnancy on maternal and perinatal outcomes at RSI Aminah Blitar. A retrospective cross-sectional design was employed using purposive sampling of secondary data from 52 medical records. The independent variable was teenage pregnancy, while the dependent variables were maternal and perinatal outcomes. Data were analyzed using the Chi-square statistical test. High frequencies of complications were observed: anemia (87%), preeclampsia (85%), and premature rupture of membranes (PROM) (73%). Perinatal outcomes included prematurity (60%), low birth weight (LBW) (52%), and asphyxia (56%). Chi-square analysis revealed that teenage pregnancy significantly influenced maternal outcomes such as anemia (p=0.001), preeclampsia (p=0.000), and PROM (p=0.000). However, no significant correlation was found with instrumental delivery (p=0.887), prolonged labor (p=0.636), or postpartum hemorrhage (p=0.168). Regarding perinatal outcomes, teenage pregnancy significantly affected prematurity, LBW, and asphyxia (all p=0.000). Teenage pregnancy is strongly associated with adverse maternal and neonatal outcomes. There is an urgent need for collaborative support from healthcare providers and families to ensure high-quality midwifery care, aiming to mitigate complications from gestation through delivery.